The Cross-sectional and Longitudinal Association between Perceived Neighborhood Walkability Characteristics and Depressive Symptoms in Older Latinos: The “¡Caminemos!” Study - Hernandez, Rosalba (J Aging Health, 2014)
OBJECTIVES: Evaluate the cross-sectional and longitudinal association between perceived walkability-related neighborhood characteristics (e.g., traffic safety) and depressive symptoms among community-dwelling older Latino adults. METHODS: We used baseline, 12-month, and 24-month in-person interview data collected from Latinos aged ≥60 years participating in an exercise intervention at 27 senior centers (n=570). RESULTS: In cross-sectional analyses, lower perceived neighborhood crime, indicative of greater neighborhood walkability, was associated with a lower odds of elevated symptoms of depression [OR=0.90; 95%CI=0.82, 0.996; p=0.04] after adjusting for demographic characteristics, linguistic acculturation, and medical comorbidities. Associations between Neighborhood Environment Walkability scales and incident depressive symptoms at 12- and/or 24-months were not statistically significant, but the point estimate for crime safety was consistent with cross-sectional findings [OR=0.83; 95%CI=0.64, 1.07; p=0.16], suggesting a protective effect for lower perceived neighborhood crime. DISCUSSION: Lower perceived neighborhood crime is associated with reduced presence of elevated symptoms of depression in older Latinos.